Alcohol and cancer: the role of cytochrome P-4502E1 - Helmut K. Seitz; Bernardo Moreira; Manuela Neuman (Nutrimentum et Curae)
Chronic alcohol consumption is a risk factor for tumours of the oral cavity, pharynx, larynx, oesophagus, liver, colorectum and the female breast. Various mechanisms contribute to alcohol-mediated carcinogenesis, including the action of cytochrome P-4502E1 (CYP2E1). CYP2E1 is one of 57 cytochrome P450 enzymes that are responsible for over 90% of the redox reactions of chemicals, including drugs, vitamins, steroids, chemical carcinogens, and industrial compounds. CYP2E1 is an important constituent of microsomal ethanol oxidation and is significantly induced by chronic ethanol consumption, which results in an increase of ethanol oxidation. CYP2E1 is present in almost all tissues, but predominantly in the liver. The increase of CYP2E1 following chronic ethanol consumption results in an enhanced activation of a variety of environmental procarcinogens present in food and especially tobacco smoke. CYP2E1 is also responsible for the degradation of retinol and retinoic acid (RA), which is associated with changes in cell differentiation, cell proliferation and apoptosis, leading to a precancerous cell cycle behaviour. Subsequently, CYP2E1 generates reactive oxygen species (ROS), which either bind directly to DNA or which result in lipid peroxidation (LPO) with LPO products such as 4-hydroxy-nonenal and malondialdehyde. These compounds can bind to DNA and may form highly carcinogenic etheno DNA-adducts. Thus, the induction of CYP2E1 by chronic alcohol ingestion is an important factor to trigger ethanol-mediated carcinogenesis.